2022
DOI: 10.1101/2022.02.21.481345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mucosal Immunization of Cynomolgus Macaques with Adenoviral Vector Vaccine Elicits Neutralizing Nasal and Serum Antibody to Several SARS-CoV-2 Variants

Abstract: The emergence of SARS-CoV-2 variants continues to be a major obstacle for controlling the global pandemic. Despite the currently authorized SARS-CoV-2 vaccines ability to reduce severe disease and hospitalization, new immunization strategies are needed that enhance mucosal immune responses, inhibit community transmission, and provide protection against emerging variants. We have developed a mucosally delivered, non-replicating recombinant adenovirus vector (rAd5) vaccine, that has proven efficacy in the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 24 publications
9
5
0
Order By: Relevance
“…Here we report rAd5 SARS-CoV-2 vaccines are highly immunogenic in AGMs and elicit cross-reactive functional antibody responses in the circulation and mucosal surfaces, confirming our previous immunogenicity results in Cynomolgus macaques [20]. We observed that all rAd5 vaccine candidates tested were able to generate cross-reactive antibody responses to mismatched antigens.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here we report rAd5 SARS-CoV-2 vaccines are highly immunogenic in AGMs and elicit cross-reactive functional antibody responses in the circulation and mucosal surfaces, confirming our previous immunogenicity results in Cynomolgus macaques [20]. We observed that all rAd5 vaccine candidates tested were able to generate cross-reactive antibody responses to mismatched antigens.…”
Section: Discussionsupporting
confidence: 91%
“…3B). This result confirmed our earlier findings in a Cynomolgus macaque model, that mucosal administration of ED90 generates cross-reactive functional antibody in the serum [20]. Furthermore, the neutralizing serum antibody responses observed were similar to what has been reported with other adenoviral and mRNA vaccines [21,22].…”
Section: Robust Cross-reactive Nasal Iga Is Elicited Following Mucosa...supporting
confidence: 91%
“…Furthermore, future work should include challenging mucosally vaccinated hamsters with the Delta and Omicron variants and other variants of concern. In terms of future human studies, a clinical trial with the vaccine construct used in this hamster study is predicted to improve the mucosal antibody response rate because studies in nonhuman primates have shown improved antibody responses compared to the original vaccine tested in humans (30).…”
Section: Discussionmentioning
confidence: 99%
“…The first assumes that that the oral vaccine is equally effective as the existing mix of intramuscular vaccines and performs similarly against transmission, therefore isolating only uptake changes as translating to health impact. The second scenario, based upon clinical evidence, presents a scenario where the oral vaccine is an additional 50% effective against transmission and any infection compared with the existing mix of intramuscular vaccines in addition to the increased uptake rates observed in scenario 2 when compared with intramuscular vaccines [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in the primary intervention scenario, we assume that an oral vaccine would offer the same protection against transmissibility of COVID-19 as the intramuscular vaccines. To take into account early clinical evidence, we also model a second intervention scenario where marginal oral vaccine cases exhibit a 50% reduction the relative risk of any infection compared with intramuscular vaccines [16,17].…”
Section: Epidemiological Inputsmentioning
confidence: 99%